Pets, protected animals and farm animals: three perceptual spaces of animal abuse - Vera, Andrea; Martín, Ana M.; Hess-Medler, Stephany; Hernández, Bernardo (Frontiers in Psychology, 2025)
Increased public and political attention to animal abuse has led to changes in legislation that recognize animals as sentient beings. Abusing animals is legally classified in Spain as an environmental crime against flora, fauna and protected areas. Consequently, research into human-animal relationships and animal abuse has also increased. Stereotypes about animals influence how humans treat them. The aim of this study is to analyze the similarities and differences of the perceptual spaces that people spontaneously construct when considering the abuse of protected animals, pets and farm animals, and then to compare them with the space of a prototypical environmental crime such as illegal dumping. Participants were 528 men and women aged between 18 and 88 years old, mostly resident in a highly environmentally protected territory. They completed an online questionnaire containing scenarios, based on press releases, of the four categories of environmental crime. Each participant was randomly asked to rate the scenarios from one of these categories in terms of severity, justification, indignation, intentionality, punishment, likelihood of personal intervention and calling the police. The questionnaire also included questions on socio-demographic data and a social desirability scale. Data were analyzed using multidimensional scaling and the results showed that a three-dimension solution was the best for the four perceptual spaces. However, the content, label and order in which each dimension emerged in the shaping of each space varied. Most pet abuse scenarios were perceived as highly reprehensible and deliberate, with the abuse of dogs and cats being more unjustified and deserving personal intervention than of other companion animals. Scenarios involving the abuse of protected and farm animals elicited less consistent reactions, influenced by the perception of their instrumentality for humans, such as for food or profit. The comparison with illegal dumping suggests that animal abuse is an environmental crime, but with specific characteristics. In contrast with other environmental crimes, its victims are sentient beings and the harm they suffer is both observable and immediate. Future research should explore, in diverse samples and territories, the key variables for effective interventions to prevent and control the social problem of animal abuse.